Validation of Motivational Factors for Sports Activities in University Students through SEMPLS - Santi-Huaranca, Inés (2018)
The objective of this research work is to evaluate the scale of motivational factors (appearance, competence, enjoyment, fitness and social) for sport activities using SEMPLS multivariate methods in order to verify the importance of the reliability and validity of the measurement model, based on a construct. The sample usedconsisted of 401 university students from administrative sciences programs and related programs of a Peruvian university. The results found report an average variance extracted of 69.5% for each of the variables and values below the point 0.90 (moderate) for the second order discriminant validity for the HTMT criterion (Heterotrait -Monotrait).